Bibliometric Perspective on Central Serous Chorioretinopathy: The Top 100 Most Citated Manuscripts: Doi: 10.36351/pjo.v39i3.1624 - Boz, Ali Altan Ertan; Kocamis, Sucattin Ilker (Pakistan Journal of Ophthalmology, 2023)
Purpose: To investigate 100 most cited manuscripts according to a bibliometric perspective via the Visualization of Similarities (VOS) viewer to learn about the trends of CSC in the past 20 years. Study Design: Bibliometric analysis. Place and Duration of Study: Sakarya University Training and Research Hospital, Turkey. Methods: The bibliometric database of the Web of Knowledge was used and keywords ‘central serous chorioretinopathy’ and ‘serous choroidopathy’ and ‘CSCR’ were entered into the search area. The retrieved manuscripts were arranged according to the number of total citations since publication to identify the 100 most-cited manuscripts. They were investigated for the total number of citations, type and name of the journal, year of publication, names of the first authors, country of origin, type of study, and main topic. The Visualization of Similarities (VOS) viewer was used to establish and visualize the bibliometric networks in this study. Results: The search retrieved 2069. Majority of the 100 most-cited manuscripts were published in the leading ophthalmology journals (96%). They were written by 477 authors. Spaide RF, Yannuzzi LA, and Eandi CM were the top three authors. The most frequently publishing country was USA (27%) and the most productive institutions were identified in USA and Holland. The most common topics were imaging (41%), such as optical coherence tomography (21%) and optical coherence tomography angiography (2%). Eleven of the 100 most-cited manuscripts were published in 2015. Conclusion: Bibliometric analysis showed that CSC is an important topic and the most cited manuscripts are published in leading ophthalmology journals.